Radiation Oncology's Place in Payment Reform: ASTRO Advocates for a Place at the Table. Issue 12 (December 2021) - Hubbard, Anne; Mantz, Constantine; Mohideen, Najeeb; Hartsell, William; Thaker, Nikhil G.; Orio, Peter; Yashar, Catheryn; Kavadi, Vivek; Kavanagh, Brian; Adler, Dave
Abstract : In its current form, the Radiation Oncology Model (RO Model) prioritizes payment cuts over true value-based payment transformation. With significant modifications to the payment methodology, the reporting requirements, and recognition of the unique challenges faced by disadvantaged populations, the RO Model can protect patient access to care, preserve the physician-patient decision-making process, and ensure the delivery of high-quality, efficient radiation therapy treatment. The American Society for Radiation Oncology has spent several years advocating for a meaningful alternative payment model for radiation oncology and continues to push The Center for Medicare and Medicaid Innovation for changes to the RO Model that will recognize these key outcomes.